Anatomical analysis of foot surface from scattered data by way of local shape analysis - Chan, Tuck Seng. (2008)
This report presents the method for determining the anatomical landmarks on the foot surface from the scattered data via local shape analysis. Calculations are described for the curvature from the scanned data by using a non-contact scanner. Characteristics of the principle curvatures were plotted for the observation of their landmarks and structures. The non-contact scanner used was a 3-Dimensional scanner. During the experiments, several manifest landmarks and structures are found due to their pronounced characteristics of the principle, Gaussion and mean curvature.